Hydrodynamic self-cleaning of plate heat exchangers with spherical dimples - V. V. Takmovtsev; A. V. Ilyinkov; A. V. Shchukin; I. SH. Zaripov (Известия высших учебных заведений: Проблемы энергетики)
Method of continuous hydrodynamic cleaning of plate heat exchangers with spherical dimples by a working medium blown through bypass ducts from high-pressure zones to low-pressure zones of adjacent dimples has been developed and experimentally validated. Complex effect on dirt caused by an additional bypass jet flow and vortices generated by the main flow allows improving the quality of heat-exchange surface cleaning and prolongs the lifetime of heat exchangers.